2020
DOI: 10.1371/journal.pone.0241399
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and barriers of PrEP delivery among diverse groups of potential PrEP users in Central Uganda

Abstract: Background Scale-up of oral pre-exposure prophylaxis (PrEP) for HIV prevention in Uganda began with serodiscordant couples (SDC) and has expanded to other most at-risk populations (MARPs). We explored knowledge, acceptability, barriers and facilitators of PrEP use among potential PrEP users in four MARPs (SDC; men who have sex with men [MSM]; female sex workers [FSW], and fisher folk). Methods We administered quantitative surveys to potential PrEP users in multiple sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 18 publications
(18 reference statements)
4
32
0
Order By: Relevance
“…To build on the successes of Uganda’s 90–90–90 progress, young men who engage in transactional sex, and other high-risk sexual behaviors should be identified for prevention interventions before they acquire HIV and other STIs or at their first episode of UDS. Behavior change interventions are perennially challenging [ 25 ], but have been shown to be effective [ 26 ] so merit ongoing efforts. In particular interventions to promote consistent condom use with all partners, including transactional and non-transactional partnerships, are required [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…To build on the successes of Uganda’s 90–90–90 progress, young men who engage in transactional sex, and other high-risk sexual behaviors should be identified for prevention interventions before they acquire HIV and other STIs or at their first episode of UDS. Behavior change interventions are perennially challenging [ 25 ], but have been shown to be effective [ 26 ] so merit ongoing efforts. In particular interventions to promote consistent condom use with all partners, including transactional and non-transactional partnerships, are required [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that potential PrEP users primarily received information about HIV prevention from HCWs ( 16 ). This reliance on HCWs for information and the need for accurate knowledge to provide high-quality care highlight the importance of ongoing training as PrEP is scaled up in Uganda and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…The Barriers Study was a mixed-methods study designed to assess knowledge of PrEP and identify potential barriers and facilitators of PrEP uptake and adherence among potential PrEP users, as well as to determine HCW knowledge of PrEP and perceptions regarding preparedness and willingness to deliver PrEP services in Central Uganda. Findings on potential PrEP users are described elsewhere ( 16 ); this paper focuses on the impact of HCW training. All activities associated with HCWs occurred in English (the official language used in provision of medical care in Uganda).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PrEP has been shown to be a robust biomedical strategy to prevent HIV infection, real-life roll-out and implementation among vulnerable populations remain low. 30 , 31 , 32 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%